An AB2-type titanium-manganese-based solid hydrogen storage alloy and its preparation method
Patent Information
- Application Number
- CN202611364310.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-04
- Publication Date
- 2026-10-20
AI Technical Summary
[0012]本发明提供了一种AB2型钛锰基固态储氢合金及其制备方法,本发明通过金属Nb对合金B侧Mn元素进行浓度梯度置换改性,能够有效解决现有AB2型钛锰基储氢合金普遍存在的预活化条件严苛、长周期循环容量衰减严重、循环使用寿命短等问题
[0025]本发明与现有技术相比,至少有以下优异之处:
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0002] This invention belongs to the field of solid-state hydrogen storage, specifically relating to an AB2 type titanium-manganese-based solid-state hydrogen storage alloy and its preparation method. Background Technology
[0004] Hydrogen energy, due to its environmental friendliness, high energy density, and abundant sources, is considered one of the most promising energy carriers for achieving the "dual carbon" goal. Safe, efficient, and economical hydrogen storage technology is a key link in the large-scale application of hydrogen energy. Among solid-state hydrogen storage materials, AB2-type Laves phase hydrogen storage alloys have become one of the most promising solid-state hydrogen storage materials due to their high theoretical hydrogen storage capacity (approximately 2.0 wt%), good cycle life, and relatively low cost. Specifically, titanium-manganese (Ti-Mn) based AB2-type hydrogen storage alloys exhibit acceptable hydrogen storage capacity at room temperature, good hydrogen absorption / desorption kinetics, and low cost, showing promising application prospects in low-pressure, ambient-temperature applications such as stationary hydrogen storage, fuel cell hydrogen supply, and portable power supplies.
[0005] However, AB2-type titanium-manganese-based hydrogen storage alloys still face several key technical bottlenecks in practical applications. First, the activation conditions for this type of alloy are quite demanding. Due to the tendency for a dense metal oxide passivation layer to form on the alloy surface, hindering the dissociation and diffusion of hydrogen molecules, multiple high-pressure pre-cycles (often exceeding 5 MPa) are typically required for activation. This long activation cycle severely restricts its rapid start-up capability in practical applications. Second, the hydrogen absorption and desorption plateau of the alloy at room temperature is significant, making it difficult to fully utilize its effective hydrogen storage capacity. Furthermore, the alloy undergoes volume expansion and contraction during repeated hydrogen absorption and desorption, easily leading to cracking and gradual pulverization. With increasing cycle count, the hydrogen storage capacity decays significantly, resulting in insufficient cycle stability and affecting the material's lifespan. These problems severely limit the large-scale application of AB2-type titanium-manganese-based hydrogen storage alloys in low-temperature, low-pressure scenarios, especially in fields such as on-board hydrogen fuel cells where rapid start-up at room temperature and long-term cycle stability are crucial.
[0006] To improve the overall performance of AB2-type hydrogen storage alloys, previous studies have attempted to optimize their hydrogen storage performance through element substitution / doping. A-side element substitution (e.g., Zr partially replacing Ti) can adjust the alloy's lattice parameters and phase stability, improving hydrogen absorption / desorption plateau characteristics; B-side element substitution (e.g., V partially replacing Mn) can enhance the alloy's hydrogen storage capacity and hydrogen absorption kinetics; adding rare earth elements (e.g., La, Ce) can improve the alloy's activation performance and low-temperature kinetics; and substituting Fe with Ni can improve cycling performance. However, existing modification methods still have significant limitations in simultaneously achieving rapid room-temperature activation and ultra-long cycle life: rare earth doping improves activation performance but has limited effect on cycle stability; Ni substitution improves cycle performance but its improvement on activation performance is not significant; and while selective V substitution can synergistically improve hydrogen storage capacity and kinetics, there is still room for improvement in ultra-long cycle retention.
[0007] Patent CN122327064A discloses a Ce rare-earth modified AB2-type titanium-manganese-based hydrogen storage alloy. By doping with trace amounts of rare-earth Ce, a Ce-rich second phase is formed at the alloy grain boundaries, disrupting the dense surface oxide passivation film. This allows the cast alloy to be activated at room temperature without annealing, and broadens the material's low-temperature storage range. However, this modification scheme relies on rare-earth raw materials, which are concentrated in mineral resources and have high purification costs, hindering large-scale commercialization. Furthermore, the patent does not verify the alloy's ultra-long cycle stability, making it difficult to simultaneously meet the dual requirements of easy activation and long service life.
[0008] Patent CN109957699A discloses a Nb-containing titanium-manganese-based hydrogen storage alloy. This patent uses Nb as an A-site dopant, primarily to optimize alloy platform characteristics and reduce raw material costs. However, this approach does not modify the B-site Mn by replacing Nb, requiring high-pressure pre-activation of the alloy. Furthermore, it lacks verification of long-cycle hydrogen absorption / desorption performance exceeding a thousand cycles. Most existing publicly disclosed Nb-modified AB2-type titanium-manganese-based hydrogen storage alloy technologies focus on doping or replacing A-site elements, failing to disclose a modification approach using Nb to gradient replace B-site Mn. This approach cannot eliminate the requirement for high-pressure pre-activation and lacks supporting data on long-cycle durability at the thousand-cycle level.
[0009] In summary, existing modification technologies still struggle to simultaneously achieve the comprehensive performance requirements of low cost, room temperature activation-free operation, and ultra-long cycle life. While rare earth modification schemes can achieve room temperature activation, they rely on rare earth resources, resulting in high raw material costs and a lack of long-cycle data support. Existing Nb-modified AB2-type titanium-manganese-based hydrogen storage alloys all focus on doping or substitution at the A-site, without using Nb to perform gradient substitution modification of Mn at the B-site. The alloys still require high-pressure pre-activation treatment and lack long-cycle durability verification at the thousand-cycle level.
[0010] In view of this, the present invention is hereby proposed. Summary of the Invention
[0012] This invention provides an AB2-type titanium-manganese-based solid hydrogen storage alloy and its preparation method. This invention modifies the B-side Mn element of the alloy by using a concentration gradient substitution of metallic Nb, which can effectively solve the problems of harsh pre-activation conditions, severe capacity decay over long cycles, and short cycle life that are common in existing AB2-type titanium-manganese-based hydrogen storage alloys.
[0013] To achieve the above objectives, the present invention employs the following technical solution:
[0014] An AB2-type titanium-manganese-based solid hydrogen storage alloy and its preparation method, wherein the chemical formula of the AB2-type titanium-manganese-based hydrogen storage alloy is: Ti 0.9 Zr 0.1 Mn 1.45-x V 0.4 Fe 0.15 Nb x , where x is the atomic ratio, satisfying 0.02≤x≤0.15.
[0015] A method for preparing an AB2 type titanium-manganese-based hydrogen storage alloy, specifically implemented according to the following steps:
[0016] Step 1: Convert the atomic percentage in the chemical formula to the mass percentage, and weigh and mix the pure metal raw materials of each component based on this.
[0017] Step 2: The raw materials mixed in Step 1 are melted in a vacuum arc melting furnace to obtain a cast alloy. The cast alloy obtained by melting is cooled with a water-cooled copper mold to prepare a Ti-Zr-Mn-V-Fe-Nb multi-element hydrogen storage alloy.
[0018] Furthermore, the specific steps for step 2 are as follows:
[0019] The proportioned raw materials are mixed and placed in a water-cooled copper crucible in a vacuum arc melting furnace. A vacuum of 3 × 10⁻⁶ is then applied. -3 After Pa, argon gas is introduced into the vacuum chamber until the chamber pressure is 0.05 MPa. The current for each melting is between 650 A and 800 A, the melting time is 60-80 s, and the melting temperature is maintained at about 1723 K. To ensure the uniformity of the alloy composition, the ingot is turned over and melted 5 times. After the melting is completed, it is cooled with the water-cooled copper mold for 30 minutes.
[0020] The AB2 type Ti-Zr-Mn-V-Fe-Nb multi-element hydrogen storage alloy prepared according to the above-mentioned preparation method of AB2 type titanium-manganese-based hydrogen storage alloy has a crystal lattice structure of C14 Laves single phase.
[0021] Furthermore, the lattice constants a of the C14 Laves single phase of the AB2 type Ti-Zr-Mn-V-Fe-Nb multi-element hydrogen storage alloy are 4.87391-4.89910 Å, c is 8.00448-8.06700 Å, and the volume V is 164.67-167.68 Å. 3 .
[0022] Furthermore, the AB2 type Ti-Zr-Mn-V-Fe-Nb multi-element hydrogen storage alloy can achieve a maximum hydrogen storage capacity of 1.90 wt% and an effective hydrogen storage capacity of 1.77 wt% under hydrogen pressure conditions of 298 K and 3.5 MPa.
[0023] Furthermore, the AB2 type Ti-Zr-Mn-V-Fe-Nb multi-element hydrogen storage alloy has a hydrogen absorption plateau pressure of 0.25-0.59 MPa and a hydrogen release plateau pressure of 0.15-0.39 MPa at a temperature of 298 K.
[0024] Furthermore, the AB2 type Ti-Zr-Mn-V-Fe-Nb multi-element hydrogen storage alloy exhibits optimal comprehensive hydrogen storage performance when the replacement amount x=0.05. Its maximum hydrogen storage capacity reaches 1.81 wt% at 298 K and 3.5 MPa hydrogen pressure, with an effective hydrogen storage capacity of 1.68 wt%. The hydrogen desorption activation energy is 9.81 kJ / mol. Simultaneously, its capacity retention rate is 97.74% after 1000 hydrogen absorption / desorption cycles and still reaches 92.89% after 3000 cycles.
[0025] Compared with the prior art, the present invention has at least the following advantages:
[0026] This invention employs a low-cost Nb element to perform gradient substitution modification on the B-side Mn of AB2-type titanium-manganese-based alloys, abandoning the rare-earth doping route. It achieves synergistic control of crystal lattice parameters, hydrogen diffusion channels, and hydride thermodynamic stability within a Ti-Zr-Mn-V-Fe pentagonal C14 Laves phase system. This modification scheme completely eliminates the high-temperature, high-pressure pre-activation process required for traditional titanium-manganese-based alloys, directly achieving room-temperature activation-free hydrogen absorption. The optimal alloy ratio achieves a reversible hydrogen storage capacity of 1.68 wt.% at 298 K and 3.5 MPa hydrogen pressure. Furthermore, its capacity retention rate is 97.74% after 1000 hydrogen absorption / desorption cycles and still reaches 92.89% after 3000 cycles, effectively solving the industry pain points of traditional AB2-type alloys, such as stringent room-temperature pre-activation conditions and rapid capacity decay over long cycles. The resulting alloy has abundant raw material reserves and a mature and easily mass-producible preparation process. It also features room temperature activation-free operation, high reversible hydrogen storage capacity, moderate equilibrium pressure, and ultra-long cycle life, providing a complete modification technology route and theoretical support for the development of low-cost, long-life, and easily activated commercial AB2-type solid hydrogen storage alloys. Attached Figure Description
[0028] Figure 1 The image shows the XRD pattern of the Ti-Zr-Mn-V-Fe-Nb multi-element hydrogen storage alloy prepared in Example 1 of this invention.
[0029] Figure 2 The image shows the isothermal hydrogen absorption and desorption curves of the Ti-Zr-Mn-V-Fe-Nb multi-element hydrogen storage alloy prepared in Example 1 of the present invention without activation treatment under a hydrogen pressure of 3 MPa (temperature of 298K-318K).
[0030] Figure 3 The image shows the hydrogen absorption and desorption PCT curves at 298 K for the Ti-Zr-Mn-V-Fe-Nb multi-element hydrogen storage alloy prepared in Example 1 of this invention.
[0031] Figure 4 In Embodiment 2 of the present invention, Ti 0.9 Zr 0.1 Mn 1.40 V 0.4 Fe 0.15 Nb 0.05 (Nb5) alloy hydrogen absorption and desorption cycle curve for 1000 cycles.
[0032] Figure 5 In Embodiment 2 of the present invention, Ti 0.9 Zr 0.1 Mn 1.40 V 0.4 Fe 0.15 Nb 0.05(Nb5) alloy 3000 hydrogen absorption and desorption cycle curves. Detailed Implementation
[0034] To further illustrate the present invention, the following description, in conjunction with embodiments and accompanying drawings, is provided. It should be understood that the embodiments are implementations based on the technical solutions of the present invention, providing detailed implementation methods and specific operating procedures. These are merely for further illustrating the features and advantages of the present invention and are not intended to limit the scope of the claims. The protection scope of the present invention should include all the contents of the claims and is not limited to the following embodiments.
[0035] Example 1:
[0036] Prepare a B-site Nb-substituted AB2-type titanium-manganese-based hydrogen storage alloy. The chemical formula of the AB2-type titanium-manganese-based hydrogen storage alloy is: Ti 0.9 Zr 0.1 Mn 1.45-x V 0.4 Fe 0.15 Nb x , where x is the atomic ratio, satisfying 0.02≤x≤0.15.
[0037] Step 1: Convert the atomic percentage in the chemical formula to the mass percentage, and weigh and mix the pure metal raw materials of each component based on this.
[0038] Step 2: Mix the raw materials prepared in Step 1 and place them in a water-cooled copper crucible in a vacuum arc melting furnace. Evacuate the furnace to a vacuum level of 3 × 10⁻⁶. -3 After Pa, argon gas was introduced into the vacuum chamber until the chamber pressure reached 0.05 MPa. The current for each melting was between 650 A and 800 A, the melting time was 60-80 s, and the melting temperature was maintained at approximately 1723 K. To ensure the uniformity of the alloy composition, the ingot was turned over and melted 5 times. After the melting was completed, the ingot was cooled for 30 minutes with a water-cooled copper mold to obtain Ti. 0.9 Zr 0.1 Mn 1.45-x V 0.4 Fe 0.15 Nb x A multi-element hydrogen storage alloy, where x is the atomic ratio, satisfying 0.02≤x≤0.15.
[0039] For the prepared Ti 0.9 Zr 0.1 Mn 1.45-x V 0.4 Fe 0.15 Nb x (0.02≤x≤0.15) multi-element hydrogen storage alloy, XRD diffraction test performed. Figure 1 Ti prepared in Example 1 of this invention0.9 Zr 0.1 Mn 1.45-x V 0.4 Fe 0.15 Nb x The XRD pattern of the (0.02≤x≤0.15) multi-element hydrogen storage alloy shows that the AB2 type Ti-Zr-Mn-V-Fe-Nb multi-element hydrogen storage alloy has a C14 Laves single-phase crystal structure. Furthermore, the lattice constants a, c, and volume V of the C14 Laves single phase of the AB2 type Ti-Zr-Mn-V-Fe-Nb multi-element hydrogen storage alloy are 4.87391-4.89910 Å, respectively. 3 .
[0040] Prepared Ti 0.9 Zr 0.1 Mn 1.45-x V 0.4 Fe 0.15 Nb x (0.02≤x≤0.15) Multi-element hydrogen storage alloy, manually crushed, then sieved using a 100-mesh metal sieve. 1.0 gram was taken for each hydrogen storage test and subjected to isothermal hydrogen absorption and desorption tests and room temperature (298K) hydrogen absorption and desorption PCT tests. Figure 2 Ti prepared in Example 1 of this invention 0.9 Zr 0.1 Mn 1.45-x V 0.4 Fe 0.15 Nb x (0.02≤x≤0.15) Isothermal hydrogen absorption and desorption curves of the multi-element hydrogen storage alloy. As can be seen from the figure, the Ti alloy prepared in the examples... 0.9 Zr 0.1 Mn 1.45-x V 0.4 Fe 0.15 Nb x (0.02≤x≤0.15) Multi-element hydrogen storage alloys have activation-free characteristics and do not require high-pressure, high-temperature pre-cycling treatment. As long as the temperature conditions are matched, they can absorb hydrogen upon initial contact with hydrogen. Figure 3 Ti prepared in Example 1 of this invention 0.9 Zr 0.1 Mn 1.45-x V 0.4 Fe 0.15 Nb x(0.02≤x≤0.15) PCT curves of hydrogen absorption and desorption of multi-element hydrogen storage alloy at room temperature (298K). As can be seen from the figure above, the maximum hydrogen storage capacity at room temperature (298K) can reach 1.90 wt%, the effective hydrogen storage capacity can reach 1.77 wt%, the hydrogen absorption plateau pressure is 0.25-0.59 MPa, and the hydrogen desorption plateau pressure is 0.15-0.39 MPa.
[0041] Example 2:
[0042] Ti 0.9 Zr 0.1 Mn 1.40 V 0.4 Fe 0.15 Nb 0.05 (Nb5) alloy cycle life test.
[0043] Figure 4 and Figure 5 Ti in Example 2 0.9 Zr 0.1 Mn 1.40 V 0.4 Fe 0.15 Nb 0.05 (Nb5) alloy hydrogen absorption and desorption cycle curves for 1000 and 3000 cycles. From Figure 3 As can be seen, the alloy achieves a maximum hydrogen storage capacity of 1.81 wt% and an effective hydrogen storage capacity of 1.68 wt% at 298 K and 3.5 MPa hydrogen pressure. Figure 4 and Figure 5 As can be seen, the capacity retention rate of this alloy is 97.74% after 1000 hydrogen absorption and desorption cycles, and still reaches 92.89% after 3000 hydrogen absorption and desorption cycles, demonstrating excellent long-cycle service stability.
[0044] The AB2-type titanium-manganese-based hydrogen storage alloy prepared by this invention possesses room-temperature activation-free characteristics, high reversible hydrogen storage capacity, and ultra-long cycle life. This invention precisely adjusts the C14 Laves phase lattice parameters, hydrogen atom diffusion channels, and hydride thermodynamic stability by gradient substitution of Mn atoms on the B-side with non-rare-earth Nb elements at the B-site, ensuring high effective hydrogen storage capacity while completely eliminating the stringent high-pressure pre-activation process of traditional titanium-manganese-based alloys. Simultaneously, it effectively improves the hydrogen absorption and desorption plateau characteristics, significantly suppressing capacity decay during long-cycle cycles, thus overcoming the technical challenges of difficult room-temperature activation and insufficient cycle life in traditional AB2-type titanium-manganese-based hydrogen storage alloys. The modifying elements used in this invention are abundant and the raw material costs are controllable. The arc melting preparation process is mature and easily scalable, providing a complete modification technology route and theoretical support for developing low-cost, long-life, and easily activated commercial AB2-type solid-state hydrogen storage alloys.
[0045] The above embodiments demonstrate that the AB2 type titanium-manganese based solid hydrogen storage alloy and its preparation method of the present invention achieve room temperature activation-free, high reversible hydrogen storage capacity and excellent cycle durability through B-site element substitution modification, and have good prospects for industrial application in vehicle-mounted solid hydrogen storage devices.
[0046] The specific embodiments described above further illustrate the purpose, technical solution, and beneficial effects of the present invention. It should be understood that the above descriptions are merely preferred embodiments of the present invention and are not intended to limit the invention. Any modifications, equivalent substitutions, or improvements made within the spirit and principles of the present invention, based on the component design concepts disclosed herein, should be included within the scope of protection of the present invention.
Claims
1. An AB2-type titanium-manganese-based solid hydrogen storage alloy and its preparation method, characterized in that, The chemical formula for the AB2 type titanium-manganese-based hydrogen storage alloy is: Ti 0.9 Zr 0.1 Mn 1.45-x V 0.4 Fe 0.15 Nb x , where x is the atomic ratio, satisfying 0.02≤x≤0.
15.
2. The AB2-type titanium-manganese-based solid hydrogen storage alloy and its preparation method according to claim 1, characterized in that, The specific steps are as follows: Step 1: Convert the atomic percentage in the chemical formula to the mass percentage, and weigh and mix the pure metal raw materials of each component based on this. Step 2: The raw materials mixed in Step 1 are melted in a vacuum arc melting furnace to obtain a cast alloy. The cast alloy obtained by melting is cooled with a water-cooled copper mold to prepare a Ti-Zr-Mn-V-Fe-Nb multi-element hydrogen storage alloy.
3. The AB2-type titanium-manganese-based solid hydrogen storage alloy and its preparation method according to claim 1, characterized in that, The specific steps for step 2 are as follows: Step 2.1: Mix the proportioned raw materials and place them in a water-cooled copper crucible in a vacuum arc melting furnace, then evacuate to a vacuum level of 3×10⁻⁶. -3 After Pa, argon gas is introduced into the vacuum chamber until the chamber pressure is 0.05 MPa; Step 2.2: The current for each melting is between 650 A and 800 A, the melting time is 60-80 s, and the melting temperature is maintained at about 1723 K. To ensure the uniformity of the alloy composition, the ingot is turned over and melted 5 times. After the melting is completed, it is cooled with the water-cooled copper mold for 30 minutes.
4. The AB2 type titanium-manganese based solid hydrogen storage alloy and its preparation method according to any one of claims 2-3, characterized in that, The crystal structure of the AB2 type Ti-Zr-Mn-V-Fe-Nb multi-element hydrogen storage alloy is a C14 Laves single phase.
5. The AB2 type Ti-Zr-Mn-V-Fe-Nb multi-element hydrogen storage alloy according to claim 4, characterized in that, The lattice constant α of the C14 Laves single phase of the AB2 type Ti-Zr-Mn-V-Fe-Nb multi-element hydrogen storage alloy is 4.87391-4.89910 Å.
6. The AB2 type Ti-Zr-Mn-V-Fe-Nb multi-element hydrogen storage alloy according to claim 4, characterized in that, The AB2 type Ti-Zr-Mn-V-Fe-Nb multi-element hydrogen storage alloy has a maximum hydrogen absorption and storage capacity of 1.90 wt% under hydrogen pressure conditions of 298 K and 3.5 MPa.
7. The AB2 type Ti-Zr-Mn-V-Fe-Nb multi-element hydrogen storage alloy according to claim 4, characterized in that, The AB2 type Ti-Zr-Mn-V-Fe-Nb multi-element hydrogen storage alloy has an effective hydrogen storage capacity of 1.77 wt% under the conditions of 298 K and 3.5 MPa hydrogen pressure.
8. The AB2 type Ti-Zr-Mn-V-Fe-Nb multi-element hydrogen storage alloy according to claim 4, characterized in that, The AB2 type Ti-Zr-Mn-V-Fe-Nb multi-element hydrogen storage alloy has a hydrogen absorption plateau pressure of 0.25-0.59 MPa at 298 K.
9. The AB2 type Ti-Zr-Mn-V-Fe-Nb multi-element hydrogen storage alloy according to claim 4, characterized in that, The AB2 type Ti-Zr-Mn-V-Fe-Nb multi-element hydrogen storage alloy exhibits optimal comprehensive hydrogen storage performance when the replacement amount x=0.05, with a maximum hydrogen storage capacity of 1.81 wt% at 298 K and 3.5 MPa hydrogen pressure.
10. The AB2 type Ti-Zr-Mn-V-Fe-Nb multi-element hydrogen storage alloy according to claim 4, characterized in that, The AB2 type Ti-Zr-Mn-V-Fe-Nb multi-element hydrogen storage alloy, with a replacement amount x=0.05, still retains a capacity of 92.89% after 3000 hydrogen absorption and desorption cycles.
Citation Information
Patent Citations
Titanium manganese based hydrogen storage alloy with low cost and high capacity
CN109957699A
Rare earth modified easy-to-activate AB2 type hydrogen storage alloy as well as preparation method and application thereof
CN122327064A